Molecular mechanisms involved in the effects of morin in experimental hepatic encephalopathy. (25th March 2022) - Shafey, Ghada M.; Rashed, Engy R.; Zaki, Hala F.; Attia, Amina S.; El‐Ghazaly, Mona A.
Abstract: This study aimed to investigate the possible usefulness of morin flavonoid in comparison to silymarin as a hepatic/neuronal‐supportive agent with similar effects and higher bioavailability in a rat model of hepatic encephalopathy (HE). Morin effects on rat liver and brain were evaluated post‐induction of HE by thioacetamide (TAA; 200 mg/kg/day for 3 successive days). Then, the serum activities of aspartate transaminase (AST) and alanine transaminase (ALT) together with ammonia concentration were estimated to assess the liver function. Also, the degree of brain effects was evaluated via the assessment of brain contents of reduced glutathione (GSH), malondialdehyde (MDA), tumor necrosis factor‐alpha (TNF‐α), and interleukin (IL‐1β) together with glutathione peroxidase (GPx) activity. In addition, the apoptotic and inflammatory changes in brain and liver tissues were also assessed via immunohistochemical examination. Our findings revealed a promising effect of morin against HE complications; as it corrected the liver functions, attenuated the brain/liver tissue injuries, and reduced the apoptotic and inflammatory insults of HE on both organs. These effects are comparable to those of silymarin. Morin could be introduced as a promising hepato‐ and neuro‐therapeutic adjuvant in HE‐associated neuronal complications especially in cases like silymarin intolerance.